Composition of the nanosized orthorhombic O′ phase and its direct transformation to fine α during ageing in metastable β-Ti alloys. (September 2019) - Li, Tong; Lai, Minjie; Kostka, Aleksander; Salomon, Steffen; Zhang, Siyuan; Somsen, Christoph; Dargusch, Matthew S.; Kent, Damon
Abstract: The structure and chemistry of the orthorhombic O′ phase after quenching of a Ti-23 at.%Nb-2 at.%O was measured using aberration-corrected transmission electron microscopy and atom probe tomography. The nanosized O′ phase, formed in the vicinity of ω, is enriched with oxygen and slightly depleted in Nb. Upon annealing, ω dissolves and the O′ phase develops in β up to 350 °C, above which temperature it transforms to colonies of fine α phase. Another needle-like form of α with lower Nb content is thought to nucleate from Nb-lean regions related to spinodal decomposition of β. Graphical abstract: Unlabelled Image